Students’ Perception On Quizizz As Online Quiz Learning Tool - FERNANDO DE NAPOLI MARPAUNG (LPPM STKIP AL MAKSUM, 2022)
Digital technology can be used as media in the learning process. One of the innovations that can be used by a teacher in the digital learning process is the assignment or quiz to students. The quiz can be used by the teachers to figure out how far students master the material and for students, it is very useful to find out how far they master the material. Online quizzes are expected to be able to make students active towards active learning. This study looked at Quizizz as a digital game-based learning tool for doing English quizzes while learning from a distance. Its goal was to find out how students saw Quizizz as a tool for digital quiz-based learning and how it was used for formative assessment. This research uses descriptive qualitative research. The subject of the research was third semester students of STKIP AL Maksum. The data were collected using questionnaire. The questioner will be given by google form. The results of this study showed that students liked Quizizz as a digital quiz-based learning tool because it helped them learn and got them involved, had clear rules and goals, clear results and immediate feedback, and let them talk to each other. They also did well on the formative assessment quiz Quizizz in English class. Also, the activities on Quizizz let students show what they knew, got feedback, and took charge of their own learning. Key words: students’ perception, Quizizz, online quiz.